Climate Change: Risks and Coping Strategies (Sebha City as a Case Study) (Sebha University Conference Proceedings, 2024)
On September 14, 2024, the city of Sebha, the capital of southern Libya, experienced heavy rainfall that resulted in human and material losses as well as varying degrees of environmental pollution across residential neighborhoods. This was caused by a combination of natural and human factors. The city faced an extraordinary climatic event, with 63 mm of rain falling in less than 90 minutes. This report aims to analyze the impacts of climate change, particularly sudden and intense rainfall, on Sebha from various perspectives—environmental, social, psychological, and economic—and to assess the extent of the resulting damages. The study employed descriptive, analytical, and historical methods, along with quantitative statistical techniques using SPSS and technical tools such as ArcGIS. Field observation and personal interviews were also utilized. The findings reveal that Sebha suffered significant human and material losses, with two fatalities and 16 injuries reported. The geographic distribution of damages varied across 12 residential neighborhoods, with a total of 44 affected sites. Approximately 2,075 homes were damaged, representing 36.1% of the total affected sites. Furthermore, 53 roads and pathways were blocked, accounting for 43.3% of the impacted areas. Additionally, the heavy rainfall led to environmental pollution due to the mixing of accumulated rainwater with sewage and blackwater in residential neighborhoods and streets. A total of 25 contaminated sites were recorded, comprising 20.5% of the affected locations. These floods pose a significant challenge that requires collaborative efforts from both the government and civil society to address. Developing effective strategies to mitigate their impact on residents' lives and properties is essential, including improving infrastructure and raising community awareness.